Clostridium perfringens sepsis complicated by right ventricular cardiogenic shock. (May 2017) - Balan, Cosmin; Barker, Graham; Garry, David
Clostridium perfringens sepsis has been ascribed a dismal prognosis when associated with massive intravascular haemolysis. We present a 71-year-old woman's fatal case which was compounded by isolated right ventricular cardiogenic shock. In this context, combined use of transthoracic echocardiography and pulmonary artery catheter monitoring is able to yield an individualized hemodynamic resuscitation. We discuss key aspects related to right and left heart mechanical efficiency, hypothesize as to the pulmonary hypertension mechanism of our case and set to emphasize a physiologically based framework for right ventricular failure hemodynamic management.